Analisis Kualitas Pelayanan Karyawan Terhadap Kepuasan Pelanggan Pada Pt. Mitra Bina Mandiri Kecamatan Gempol Kabupaten Pasuruan - Imron, Mochammad Khoirul; Wati, Shanti Bintara; Indiati, Indiati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research intends to identify the impact of the quality of employee services on client happiness at PT. Mitra Bina Mandiri, to achieve this goal, so that a qualitative descriptive analysis method is used. This analysis is based on information that is claimed in the form of data explanations and then developed with other information to gain clarity or establish a reflection, in this case regarding the quality of employee services to client satisfaction at PT. Mandiri Bina Partners. Which is part of the quality of employee services can affect client satisfaction when making purchases. All information will be obtained from the results of observation, selection and debriefing with all parties involved in future research.